Billion dollar babies [compact disc] - Cooper, Alice, 1948-; Buxton, Glen; Bruce, Michael, 1948-; Dunaway, Dennis; Smith, Neal, 1947- (Warner Records, 2024)
The original album remastered + a live set from the Billion Dollar Babies tour, single versions, and rare tracks.